Predictive Factors for Recurrence of Papillary Thyroid Carcinoma in Children and Adolescents - Gui, Yan; Huang, Dongmei; Hou, Yun; Wei, Xudong; Zhang, Jinming; Wang, Junyi (Frontiers in Oncology, 2022)
Background The incidence of papillary thyroid carcinoma (PTC) in children and adolescents has increased, but the data on long-term outcomes are limited. There are few literatures on the clinicopathological characteristics and prognosis of PTC in children and adolescents in China. Therefore, it is necessary to identify clinicopathological features to precisely predict clinical prognosis and to help choose the optimal method and perform the best therapeutic regimen. Methods This study was a retrospective analysis of patients undergoing thyroidectomy at Tianjin Medical University Cancer Institute and Hospital. We analyzed the factors related to the clinicopathological features and prognosis of PTC in children and adolescents. Results A total of 95 juvenile PTC patients who underwent thyroidectomy were enrolled. Our research found that patients with younger age (<14 years) were predominantly multifocal and have positive preoperative thyroglobulin (Tg) and higher recurrence rate, and their number of lymph node metastases (LNMs) was more than that of the older group (14–18 years). Maximal tumor size >2 cm, T stage, and multifocality were the risk factors for LNM and the number of LNM (p < 0.05). Multivariate analysis displayed the number of central LNM as the independent risk factor for lateral LNM, and multifocality was the independent risk factor for the number of central and lateral LNM. Younger age at diagnosis, positive preoperative thyroid-stimulating hormone (TSH), maximal tumor size >2 cm, lateral LNM, number of LNM, N staging, and American Thyroid Association (ATA) pediatric risk were related to poor prognosis in PTC patients (p < 0.05). Cox regression analysis found that younger age at diagnosis and positive preoperative TSH were independent risk factors for recurrence of PTC in children and adolescents. Conclusions Our study showed that the clinicopathological characteristics of younger age compared with older age were as follows: highly aggressive, prone to metastases, and higher recurrence rate. In our opinion, patients with characteristics such as younger age at diagnosis, positive preoperative TSH, maximal tumor size >2 cm, lateral LNM, and number of LNM >5 may be considered for prophylactic or therapeutic dissection of additional metastatic LNs by high-volume surgeons to prevent and reduce the recurrence rate of patients during long-term follow-up.